Studi awal inklusi fluida pada fenokris kuarsa di Hargorojo, Bagelen, Purworejo, Jawa Tengah - okki verdiansyah (Retii, 2022)
The research focuses on dacite intrusion, in the Hargerejo area in the southern Kulonprogo Mountains and administratively in the Begelen District, Purworejo Regency, Central Java Province. The presence of a hydrothermal system in the Kulon Progo area is in the form of low-medium sulfidation epithermal in Kokap, Epithermal - Lithocap in Bagelen, and high-sulfidation epithermal in Menoreh (Magelang). In the case of the Bagelen intrusion, it is suspected that it is part of the hydrothermal system that forms the Au-Ag hydrothermal system. The research uses geological mapping methods and surface sampling on dacite rocks and laboratory observations with polarization and ore microscopy. This study focuses on the character of quartz and the presence of fluid inclusions by using the qualitative concept of fluid inclusion petrography. The lithology of the Bagelen area consists of volcanic breccias, andesite intrusions, dacites, and alluvial deposits. Petrographic analysis of dacite samples showed a porphyritic texture with 55-76% phenocrysts in the form of quartz (8-22%), hornblenda (3-11%), plagioclase (40-55%), surrounded by a bottom mass of volcanic glass and feldspar microlites. , as well as opaque minerals in the form of pyrite and residual magnetite as much as 2-5% and the base mass undergoes diagenesis and is changed to silica. Quartz is divided into types 1 and 2, indicating the presence of primary and pseudosecondary inclusion types. Quartz type 1 (qz-1) shows an irregular distribution and pseudosecondary trail with Type I, II, III inclusions. In type 2 quartz, it is seen that the inclusions are dominated by type II & III or L<V and L>V biphase, with low to high vapor densities. Inclusions in type 2 quartz show a primary pattern and are similar to the general epithermal vein fluid on the surface. The presence of fluid inclusions in the magmatic quartz at Bagelen, indicates the existence of a hydrothermal system formed due to changes in silicate character, and affects the fluid character from magmatic to hydrothermal. Epithermal or related mineralization is more influenced by the presence of type 2 quartz, and subsequent hydrothermal processes. The type of mineralization affected is intermediate sulfidation with a characteristic presence of disseminated pyrite-chalcopyrite in dacite. The fluid that affects mineralization is dominated by the epithermal system. Keyword : Exploration, Fluid, Copper, Gold, Kulon Progo